Dietary Black Soldier Fly Larvae Meal and Its Impact on the Growth Performance and Gut Health of Broilers Under an Intestinal Challenge - Yuri Katagiri Dalmoro; Guilherme Librelotto de Godoy; Jessica Cristina Agilar; Glauco Anderson Raddatz; Fernanda de Candido de Oliveira; Natieli Witt; Catarina Stefanello (Metabolites)
Background/Objectives: The use of black soldier fly (BSF) larvae meal in poultry nutrition is gaining attention as a sustainable protein source with a high nutritional value, an efficient bioconversion of organic waste, and potential functional benefits for intestinal health. This study evaluated the dietary effects of including 5% BSF larvae meal on the growth performance, nutrient digestibility, and energy utilization as well as on the intestinal integrity, gene expression, lipid profile, and short-chain fatty acid (SCFA) production of broilers under an intestinal challenge. Methods: Eight hundred one-day-old male broilers were assigned to four dietary treatments with eight replicates (25 birds/pen) and reared until day 40. Birds were fed either a Basal corn–soy diet or a BSF diet (5% BSF larvae meal replacing energy- and protein-yielding ingredients). Diets were provided to a non-challenged group and a challenged group, which was orally gavaged with Eimeria spp. on day 1 and Clostridium perfringens on days 11 and 14. The growth performance was evaluated up to day 40, while the nutrient digestibility, meat lipid profile, intestinal histomorphology, and gene expression were assessed at 21 days. The SCFAs were determined at both 21 and 40 days. Results: It was observed that the intestinal challenge induced dysbiosis and negatively affected growth performance, whereas the BSF meal inclusion partially mitigated these adverse effects. Broilers fed the BSF larvae meal showed increased cecal SCFA concentrations and a lower interleukin-6 gene expression, along with higher lauric and myristic acid levels in breast muscle (p ≤ 0.05). Conclusions: The inclusion of 5% BSF larvae meal improved performance without impairing nutrient digestibility or intestinal histomorphology, while increasing cecal concentrations of butyric and acetic acids and promoting a beneficial lipid deposition.